2020
DOI: 10.3389/fvets.2020.00427
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Borago officinalis (Borago) on Cold Restraint Stress-Induced Gastric Ulcers in Rats: A Pilot Study

Abstract: Stress is a typical body's natural defense to a generic physical or psychic change. A specific linking mechanism between ulcer onset and psycho-physical stress prolonged exposure has been reported. We decided to investigate the possible effects of Borago officinalis L. (Borago) in preventing physical (stress)-induced gastric ulcers in a rat model. Eighty male Sprague-Dawley rats were randomly divided into 16 groups, pretreated with a control solution, omeprazole (20 mg/kg), Borago methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…The expression of NMDA receptor subunits is not altered in stress-induced ulcer models. This indicates, that NMDA receptors are not directly involved in ulcer formation, but rather in protecting the gastric mucosa Di Cerbo et al (2020) . The current study also revealed that pre-injecting the NMDA receptor blocker, D-AP5, eliminated modulation of gastric function by L-Glu and NaHS.…”
Section: Discussionmentioning
confidence: 92%
“…The expression of NMDA receptor subunits is not altered in stress-induced ulcer models. This indicates, that NMDA receptors are not directly involved in ulcer formation, but rather in protecting the gastric mucosa Di Cerbo et al (2020) . The current study also revealed that pre-injecting the NMDA receptor blocker, D-AP5, eliminated modulation of gastric function by L-Glu and NaHS.…”
Section: Discussionmentioning
confidence: 92%
“…Di Cerbo et al., (2020) [62] examined the toxicity of crude methanolic extract, organic (obtained by ethyl acetate) fraction, and aqueous fraction on A31‐1‐1 cells (type of cells derived from mice embryos) at various concentrations (250, 500, and 1000 mg/kg). The organic fraction induced cytotoxic effects at 500 and 1000 mg/kg, reducing cell viability by 43.6 % and 92.1 %, respectively.…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…Different concentrations of methanolic extract and its organic (ethyl acetate) and aqueous fractions from B. officinalis leaves were administrated on stress‐induced gastric ulcers in rats [62] . The methanolic extract significantly reduced the severity and number of gastric ulcers in a dose‐dependent manner, particularly at 500 mg/kg.…”
Section: Biological and Pharmacological Activitiesmentioning
confidence: 99%
“…Mice exposed to cold-restraint stress presented gastric ulcer and inflammation ( Di Cerbo et al., 2020 ; Higashimori et al., 2021 ). Further, 15-min cold exposure in mice increased their gastric phasic activity and tone, whereas mice exposed to chronic stress presented with no gastric response ( Gourcerol et al., 2011 ).…”
Section: Introductionmentioning
confidence: 99%